A plasmonically enhanced route to faster and more energy-efficient phase-change integrated photonic memory and computing devices - Gemo, E; Faneca, J; G.-C. Carrillo, S; Baldycheva, A; Pernice, WHP; Bhaskaran, H; Wright, CD (AIP Publishing, 2021)
Over the past 30 years or more, chalcogenide phase-change materials and devices have generated much scientific and industrial interest, particularly as a platform for non-volatile optical and electronic storage devices. More recently, the combination of chalcogenide phase-change materials with photonic integrated circuits has begun to be enthusiastically explored, and among many proposals, the all-photonic phase-change memory brings the memristor-type device concept to the integrated photonic platform, opening up the route to new forms of unconventional (e.g., in-memory and neuromorphic) yet practicable optical computing. For any memory or computing device, fast switching speed and low switching energy are most attractive attributes, and approaches by which speed and energy efficiency can be improved are always desirable. For phase-change material-based devices, speed and energy consumption are both enhanced the smaller the volume of phase-change material that is required to be switched between its amorphous and crystalline phases. However, in conventional integrated photonic systems, the optical readout of nanometric-sized volumes of phase-change material is problematic. Plasmonics offers a way to bypass such limitations: plasmonic resonant structures are inherently capable of harnessing and focussing optical energy on sub-wavelength scales, far beyond the capabilities of conventional optical and photonic elements. In this work, we explore various approaches to combine the three building blocks of Si-photonics, resonant plasmonic structures, and phase-change materials to deliver plasmonically enhanced integrated phase-change photonic memory and computing devices and systems, underlining the inherent technical and theoretical challenges therein.